2021
DOI: 10.3390/su132413549
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Service Modelling to Support Nature-Based Flood Water Management in the Vietnamese Mekong River Delta

Abstract: Deltas are among the most productive and diverse global ecosystems. However, these regions are highly vulnerable to natural disasters and climate change. Nature-based solutions (Nbs) have been increasingly adopted in many deltas to improve their resilience. Among decision support tools, assessment of ecosystem services (ES) through spatially explicit modelling plays an important role in advocating for Nbs. This study explores the use of the Land Utilisation and Capability Indicator (LUCI) model, a high-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 79 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…The Mekong Delta has been of critical importance for rice production for decades and will most likely continue to be so (Dang et al 2021 ; Lan and Nguyen. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Mekong Delta has been of critical importance for rice production for decades and will most likely continue to be so (Dang et al 2021 ; Lan and Nguyen. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the farmers also felt that high dikes had decreased the amounts of aquatic organisms, especially fish and that this had decreased the biodiversity because a loss of connectivity and habitats (cf. Dang et al 2021 ). Nguyen et al ( 2018 ) found significant decreases in the numbers of native fish and vegetables in areas enclosed by high dykes in An Giang.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited detail in soil physical, chemicals and hydraulic data is common in tropical countries . Some results from the case study, e.g., drainable water, plant available water, saturated hydraulic conductivity, were used for the application of the LUCI to map multiple ecosystem services in the VMD (Dang et al, 2021b).…”
Section: Vietnamese Mekong Delta Case Studymentioning
confidence: 99%
“…As articulated in the first paragraph of section 4.3 and also in Dang et al (2021b) "This is not recommended for final application of LUCI but can be a useful way of exploring model capacities and preliminary results for your region. Careful consideration should be given to whether the supported datasets span similar land use or soil types to those present in your region.…”
Section: Matching Vmd Soil and Lulc Datasets To Supported/already Par...mentioning
confidence: 99%